2018
DOI: 10.1002/jid.3377
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Determinants of Saving in Ghana: Does Financial Literacy Matter?

Abstract: Domestic savings remain low in Ghana despite several attempts to improve this situation. Whereas existing studies on private savings have identified several determinants, the role of financial literacy in saving decisions has not been explored. In this paper, we build on existing studies and provide evidence supporting our hypothesis that financial literacy is key to promoting domestic saving. The study relies mainly on primary data, and the binary probit regression model is employed as the estimation techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 46 publications
6
40
1
Order By: Relevance
“…Other factors that have strong effects on financial inclusion, according to the study, are age, rural–urban location, education and gender. In another study that examines the impact of financial literacy on domestic savings in Ghana, Baidoo, Boateng, and Amponsah () show that financial literacy level of an individual positively affects the individual's decision to save. The authors also identify income distributions, household size and the sector an individual is employed as other critical determinants of savings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other factors that have strong effects on financial inclusion, according to the study, are age, rural–urban location, education and gender. In another study that examines the impact of financial literacy on domestic savings in Ghana, Baidoo, Boateng, and Amponsah () show that financial literacy level of an individual positively affects the individual's decision to save. The authors also identify income distributions, household size and the sector an individual is employed as other critical determinants of savings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The people save their money for different purposes. Saving is beneficial not only for the individuals but also for the whole country and it helps in infrastructure development and long-run investments in the country likewise saving act as a hurdle for countries against financial crisis and economic downturns (Jagadeesh, 2015;Baidoo et al, 2018). Clark and Madeleine (2008) demonstrated that financial literacy and financial plans are extremely successful in defeating the reduction in saving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saving is the portion of income which is not spent on current consumptions. The consumption pattern of individuals determines their savings decisions (Browning & Crossley, 2001;Baidoo, Boateng & Amponsah, 2018). Saving is considered as a major factor that affects the economic growth of developing countries (Jagadeesh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, World Bank indicates that financial literacy in Ghana is low and this does not encourage speculative purposes for money demand (Xu & Zia, 2012) . This therefore arouses the urgent need to enhance the financial literacy level of Ghanaians as indicated in past studies (see for example, Baidoo et al, 2018;Baidoo & Akoto, 2019). Another important variable is real income.…”
Section: Cointegration Test Resultsmentioning
confidence: 94%